NGHIÊN CỨU QUÁ TRÌNH TẠO MẪU PHỤC VỤ ĐO SÓNG ĐỊA CHẤN TRONG CÁC PHA NGẬM NƯỚC CÓ ÁP SUẤT VÀ NHIỆT ĐỘ CAO VỚI MÔ HÌNH ĐỚI HÚT CHÌM - Hương, Phan Thiên (Vietnam Journal of Earth Sciences, 2011)
Measurement elastic velocity of hydrous phases at high P-T of subduction slab by multi-anvil apparatusThe relationship between seismic wave propagation velocities and water content of hydrous rock has been identified by a study at Swiss Federal Institute of Technology Zurich (ETHZ). As a result, the Earth’s deep structure can be studied by combination of seismic tomography and petrological experiment. The result was achieved by applying ultrasonic techniques under ultra high temperature - pressure condition in multi-anvil apparatus. In this paper, the study is presented including the selection of represented samples, an important requirements for hydrous samples and their synthesis method that assure the sample quality suitable for the measurement of elastic velocity in condition corresponding with high P-T in subduction slab.